The Development of TANAKA Android-based Application as an Information Media for Taka Bonerate National Park - Amelia Firdhausya Dewi; Selvia Deviv; Nur Syamsinar Munir (Ceddi Journal of Education, 2023)
This study aims to determine the development of the TANAKA application as an Android-based information media for Taka Bonerate National Park. The quality of the application was evaluated based on the ISO 9126 quality standards. The application was built using Adobe Flash CC software. Data was collected using interview techniques, questionnaires, and documentation. The application was validated by two media experts and two content experts. The application was evaluated by 30 respondents, and the data was analyzed using descriptive statistical analysis techniques. Based on the research results, an application was developed that can be used as an offline Android-based information media for Taka Bonerate National Park. According to the ISO 9126 testing, the following results were obtained: a) functionality testing using black box testing method scored 1 with an excellent category and fulfilled the functionality aspect; b) reliability testing using white box method was free from logical errors; c) portability testing on various types of smartphones and different versions of Android ran smoothly without any issues; d) usability testing with 30 respondents resulted in a percentage of 93.33%, with 28 respondents rating it as excellent and a percentage of 6.67% or 2 respondents rating.